An evaluation of the use of testamentary and Inter vivos trusts as estate-planning vehicles and the development of holistic estate-planning models involving the use of these trusts - Naidoo, Loganathan (Rhodes University, Faculty of Commerce, Department of Accounting, 2013)
Trusts are subject to multiple forms of legislative regulation dealing with taxation and governance. Trusts were widely used by planners as tax avoidance shelters. Tax legislation was amended to subject trusts, other than special trusts as defined, to the highest income tax rate of forty percent, in terms of section 5(2) of the Income Tax Act, 58 of 1962. The inter vivos trust is also subject to a wide range of anti-avoidance measures, including those contained in sub-sections (3) to (8) of section 7 of the Income Tax Act and Part X of the Eighth Schedule to the Act, as well as the general anti -avoidance measures in section 103. These measures impact negatively on the use of trusts for estate-planning purposes. The research objective was to evaluate the use of testamentary and inter vivos trusts for estate-planning purposes and to develop a holistic estate-planning model incorporating these planning instruments. Both the testamentary trust and the inter vivos trust were evaluated against broad principles of effective estate planning and the taxes and duties applicable to them. The research also reviewed the writings of financial planners on various techniques and models used for estate planning, as wells as case studies documented in the literature. The research developed and evaluated holistic estate-planning models incorporating testamentary trusts and inter vivos trusts, respectively. By neutralizing the effects of various taxes and duties, it was demonstrated that it is possible to develop an estate plan that satisfies most of the requirements of effective estate planning.
Keywords: Commission of Inquiry into Certain Aspects of the Tax Structure of South Africa; Income tax -- Law and legislation -- South Africa; Taxation -- Law and legislation -- South Africa; Trusts and trustees -- South Africa; Trusts and trustees -- Taxations -- South Africa; Estate planning -- South Africa; Estates (Law) -- South Africa; Administration of estates -- South Africa